WRESTLING PREPARATION PROCESS IN SPORTS SCHOOLS - A.T.Hasanov; A.B.Mamanazarova (Journals Park Publishing, 2022)
In this article, a survey was conducted on the problems of maintaining a contingent of children involved in freestyle wrestling in sports schools.
Keywords: Children; sports school; freestyle wrestling